ANALISIS PENGARUH PROGRAM KEWIRAUSAHAAN BERBASIS IPTEKS TERHADAP KESIAPAN BERWIRAUSAHA PADA MAHASISWA DI POLTEKKES BHAKTI SETYA INDONESIA - Ana Mardiyaningsih; Nur Ismiyati; Rina Widiastuti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Graduates students mostly oriented into a job seeker, not the job creators. There is an assumption that the preparations become entrepreneurs during college, lead to failure in passing study on university. Science and technology-based entrepreneurship education can change those assumption, so it can affect a student's readiness for entrepreneurship on 3 aspect: affective (attitude), cognitive (knowledge), and psychomotor (skills). This research aimed to analyzed the effect of science and technology-based entrepreneurship programs to changes in student readiness.This research was quasy experimental by intervented 20 tenants, the participant of Ipteks bagi Kewirausahaan (Science and Technology for Entrepreneurship) at the Polytechnic of Health Bhakti Setya Indonesia. Students attended a series of science and technology-basedentrepreneurship education program especially by approaching of herbal saintification in various kinds of products that lead to supporting therapy. The intervention consist of a motivational training program, training on creating products, internships in industry partners, and comparative study. Data was collected by questionnaire test in pre and post treatment to determine the student’s readiness changing. Data was analyzed by paired T-test. The result showed that the intervention of science and technology-based entrepreneurship programs can improve student’s readiness in entrepreneurship.Keywords: entrepreneurship, entrepreneurship readiness, student, science and technology